Servant Leadership and Innovative Work Behavior: The Role of Meaningful Work and Strengths Use - Mardhiyyah Thaib, Rosa Nabiila; Parahyanti, Endang (Journal La Sociale, 2025)
Amidst the current high global dynamics and volatility, BUMN as the spearhead of the national economy needs to strengthen its performance through innovation. However, innovation itself is still a challenge that needs to be overcome by BUMN to maximize its potential. This study aims to examine the mediating role of meaningfulness of work in the relationship between service leadership and employee innovative behavior, as well as the moderating role of the use of power. The measuring instruments used in this study consisted of a scale of innovative work behavior (α = 0.954), service leadership (α = 0.771), meaningfulness of work (α = 0.925), and use of power (α = 0.893). This study involved 366 BUMN employees who had direct superiors and were aged 20-40 years, and were selected using convenience sampling techniques. Data analysis using the PROCESS model 4 and model 14 procedures showed that meaningfulness of work mediated the relationship between service leadership and innovative work behavior. However, this study did not find a moderating effect of the use of power on the mediation effect.